The plea agreements process in the International criminal tribunal for former Yugoslavia in the light of the amnesty process in the Truth and Reconciliation commission in South Africa - Toma, Marijana (Department of Political Studies, 2014)
While many countries are facing difficulties in implementing transitional justice mechanisms, designed mainly to include different stakeholders in the process, in very few contexts have perpetrators been perceived as active participants who represent a potential resource to the process. This study examines and compares two contexts in which this has been so. Its central objective is to understand to what extent the practice of plea bargaining with perpetrators of war crimes at the International Tribunal for the Former Yugoslavia (ICTY) contributed to the process of establishing the truth about past abuses and to compare this with probably the most controversial aspect of the Truth and Reconciliation Commission in South Africa (TRC) -- granting of amnesty to the responsible for the atrocities during apartheid. Drawing on both contexts, this study argues that that acknowledgment given by perpetrators potentially constitutes a legitimate and in some contexts crucial transitional justice mechanism. The study has not examined all the issues relating to these processes, recognizing their complexity in both the historical development of the field of transitional justice and the specific features of the process in each context. The study was developed at two levels, firstly through a normative analysis of the aims and objectives of the plea bargaining process at the ICTY and amnesty process at the TRC and secondly, through historical and factual investigation of the processes and outcomes in relation to the criteria set out for processes ICTY and TRC adopted. The main aim was to analyze what were the outcomes of these two processes in terms of contributing to the process of establishment of truth. Recognizing that these processes were inherently different from each other ? one being implemented in criminal trials, and other in truth commission, it is important to note that these have been the only two examples to date to include a form of compromise with perpetrators as one of their main strategies for the process of establishing truth. While recognizing that serious criticism have been made against both institutions for this compromises, this study concludes that any truth process, if trying to be comprehensive, will have to include perpetrators, because only they can provide the most important element in dealing with the human rights violations and the one most difficult to be obtained - acknowledgment by those who actually committed the crime.